Social inequality and space in the childhood. The spatial trajectories observed in children’s play of different social positions - Castillo, Patricia (Revista de Psicología, 2011)
This work is framed into the author’s doctoral research. Drawing from Critical Geography (Garrido, 2009; Massey, 2005), it uses the method of Clinic Research Methodology (Gaulejac, 1993) to investigate through children’s playing the spatial trajectories of children in different social positions. The analysis material consists of the clinical observation of infantile playing. The results show differences in the spatial trajectories in children between 3 and 5 years old, which relate to the fears and expectations of significant others, the social reality where they are, and the children’s direct or mediated relationship with mass media.